Nerves, nodes, and neoplasia - Wang, Minjun; Ran, Censhan; Liu, Quan (Frontiers in Immunology, 2025)
Tumor immune evasion and incomplete responses to immunotherapy are some of the most significant obstacles in current cancer treatment. Since tumor-draining LNs (tdLNs) are cradles for anti-tumor immunity, and tumor-specific memory cells in tdLNs are the bona fide responders to immune-checkpoint blockade, tdLNs are increasingly valued in oncoimmunology research and cancer treatments. Recent progress has revealed that lymph nodes (LNs) are innervated and regulated by sensory and sympathetic nerve fibers. Because tumor cells, nerves, and immune cells coexist inside tdLNs—sites where anti-tumor immunity is initiated and compromised—it is critical to investigate whether tumor-neuro-immune crosstalk also occurs in these nodes. Although direct evidence in tdLNs is lacking, we synthesize emerging evidence supporting this possibility. We argue that validating this hypothesis will be essential for elucidating immune evasion mechanisms and advancing surgical and immunological strategies against tumors. In this review, we first introduce LN anatomy, highlighting its innervation by sensory and sympathetic fibers. We then examine the neural regulation of immune activities, especially those within LNs and those associated with a tumor context. We further discuss the multifaceted roles of tdLNs in tumor immunology, including orchestration of anti-tumor immunity and local immunosuppression, pre-metastatic LN remodeling, and induction of systemic tumor-specific immune tolerance. Furthermore, we look into tumor-neural interactions from two angles: tumor-induced nerve growth and activation, and neural regulation of tumor progression. Finally, we propose potential tumor-neuro-immune interactions in tdLNs, discuss current perspectives on LN handling in cancer therapy, and discuss clinical implications of the progress summarized in this review.